2017
DOI: 10.1016/j.bbamcr.2016.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Tudor-SN, a novel substrate of JNK, is involved in the efficient recruitment of Tudor-SN into stress granules

Abstract: Posttranslational modifications of certain stress granule (SG) proteins are closely related to the assembly of SGs, a type of cytoplasmic foci structure. Our previous studies revealed that the Tudor staphylococcal nuclease (Tudor-SN) protein participates in the formation of SGs. However, the functional significance of potential Tudor-SN modifications during stress has not been reported. In this study, we demonstrated that the Tudor-SN protein was phosphorylated at threonine 103 (T103) upon stimulation with ars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Previously, we found that the SND1 protein can interact and colocalize with PABP1 and regulate the FRAP dynamics of G3BP‐tracing SGs in response to arsenite sodium‐mediated oxidative stress conditions (Gao et al, ). Very recently, we found that c‐Jun N‐terminal kinase (JNK) can increase the phosphorylation of SND1 at threonine 103 (T103), which is involved in the efficient aggregation of the SND1 protein into SGs (Su et al, ). Here, we found that the assembly of SND1 granules upon heat shock stimulus in HeLa cells occurs in a microtubule transport‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we found that the SND1 protein can interact and colocalize with PABP1 and regulate the FRAP dynamics of G3BP‐tracing SGs in response to arsenite sodium‐mediated oxidative stress conditions (Gao et al, ). Very recently, we found that c‐Jun N‐terminal kinase (JNK) can increase the phosphorylation of SND1 at threonine 103 (T103), which is involved in the efficient aggregation of the SND1 protein into SGs (Su et al, ). Here, we found that the assembly of SND1 granules upon heat shock stimulus in HeLa cells occurs in a microtubule transport‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Ras GTPase activating protein SH3 domain binding protein (G3BP) is a phosphorylation dependent endoribonuclease that assembles stress granules and potentially degrades the SG mRNAs. Under oxidative stress, c-JNK phosphorylates SND1 at threonine 103, promoting the binding of its SN domain with G3BP to form stress granules [48] . It is not yet clear if the role of SND1 is limited to assembling these SGs or extends beyond that where the endonuclease activity of SND1 participates in degrading SG mRNAs.…”
Section: Snd1 and Stress Responsementioning
confidence: 99%
“…Tudor-staphylococcal nuclease (SN), also known as staphylococcal nuclease domain containing 1 (Snd1), is a highly conserved and ubiquitously expressed multifunctional protein (15)(16)(17)(18)(19)(20)(21)(22)(23). This enzyme comprises a tandem repeat of 4 SN-like domains (referred to as SN domains) at the N terminus and a fusion of a Tudor domain with a partial SN domain at the C terminus (referred to as a TSN domain) (22).…”
mentioning
confidence: 99%
“…This enzyme comprises a tandem repeat of 4 SN-like domains (referred to as SN domains) at the N terminus and a fusion of a Tudor domain with a partial SN domain at the C terminus (referred to as a TSN domain) (22). Tudor-SN is normally localized in the cytoplasm except under certain circumstances, such as stress, in which it may shuttle between the nucleus and the cytoplasm (16,19,23). This protein plays important roles in the early stage of the DNA damage response in a poly-ADP-ribosylation-dependent manner via interaction with poly (ADP-ribose) polymerase (Parp)-1 through an SN domain (23).…”
mentioning
confidence: 99%